Modeling Student Expectation Formation through SAPS: An Indicator Relationship Analysis among Arabic Language Students - M. Kholis Amrullah; Agus Riwanda; Wisetrat Wilailak; Faisal Mubarak; Fatwa Arifah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Arabic learning plays a strategic role in religious scholarship, intercultural communication, and global engagement in Indonesia. Despite extensive research on Arabic pedagogy, limited attention has been given to students’ future-oriented expectations across higher education institutions. This study investigates the expectations of Arabic language students in four Islamic universities in Metro, Indonesia, using the Scale to Assess Possible Selves (SAPS). The findings reveal that although students’ current conditions are weakly associated with their learning expectations, there is a significant collective shift toward higher future aspirations. The ideal self emerges as a strongest motivational predictor than the ought-to self, indicating that positive future self-visions play a central role in shaping engagement and long-term commitment. However, a discrepancy remains between students’ self-concepts and their actual learning experiences. The study underscores the importance of strengthening reflective mentoring, curriculum alignment, and authentic learning exposure to foster sustainable motivation, professional identity formation, and academic development among Arabic language students in the contemporary global context.